(untitled) (Homoeopathy for All, 2024)
Most of the changes your body undergoes during pregnancy are healthy and expected. Some effects of pregnancy may cause you discomfort, but many of these common discomforts can be prevented relieved by simple measures. However, you should be aware of symptoms that are not usual and may indicate a serious problem that requires careful monitoring or special treatment during your pregnancy. These conditions include diabetes, hypertension, thyroid disorders, kidney disorders and liver disorders. Liver disorders, though not very common during pregnancy need special attention and care as they can pose a risk to you or your foetus. The common liver disorders that can affect a woman during pregnancy are mentioned here with their causes, symptoms, prevention and management.